Plant-Pathogen Interactions Methods and Protocols - Birch, Paul.; Birch, Paul.; Jones, John T.; Jones, John T.; Bos, Jorunn I.B.; Bos, Jorunn I.B. (Methods in Molecular Biology, 2014)
Plant-Pathogen Interactions: Methods and Protocols, Second Edition expands upon the first edition with current, detailed protocols for the study of plant pathogen genome sequences. It contains new chapters on techniques to help identify and characterize effectors and to study their impacts on host immunity and their roles in pathogen biology. Additional chapters focus on protocols to identify avirulence and resistance genes, investigate the roles of effector targets and other defence-associated proteins in plant immunity. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols and tips on troubleshooting and avoiding known pitfalls.   Authoritative and cutting-edge, Plant-Pathogen Interactions: Methods and Protocols, Second Edition seeks to aid scientists in the further study of plant immunity.